2013
DOI: 10.1111/exd.12077
|View full text |Cite
|
Sign up to set email alerts
|

HLAE*0103X is associated with susceptibility to Pemphigus vulgaris

Abstract: Non-classical human leucocyte antigen-E (HLA-E) mediates natural killer and CD8+ T-cell activity, suggesting a role in the regulation of autoimmunity. HLA-E*0103X/*0103X has been associated with Behcet's disease and HLA-E *0101/*0103X with childhood onset diabetes. We investigated HLA-E allele status in 52 Caucasian and Ashkenazi Jewish Pemphigus vulgaris (PV) patients and 51 healthy controls by restriction fragment length polymorphism-polymerase chain reaction and amplification refractory mutation system. Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…The HLA-E*01:03/ 01:03 genotype has been associated with increased risk of Behc¸et's disease (BD) [18]. Moreover, this genotype was found to be a risk factor for pemphigus vulgaris (PV) development [20]. Additionally, the frequency of the HLA-E*01:03/*01:03 genotype was elevated in patients with multiple sclerosis (MS) [21] and HLA-E*01:01/*01:03 heterozygosity has been associated with severe and earlyonset manifestations of type I diabetes mellitus (T1D) [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HLA-E*01:03/ 01:03 genotype has been associated with increased risk of Behc¸et's disease (BD) [18]. Moreover, this genotype was found to be a risk factor for pemphigus vulgaris (PV) development [20]. Additionally, the frequency of the HLA-E*01:03/*01:03 genotype was elevated in patients with multiple sclerosis (MS) [21] and HLA-E*01:01/*01:03 heterozygosity has been associated with severe and earlyonset manifestations of type I diabetes mellitus (T1D) [19].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of this recognition pathway, it was proposed that the HLA-E*01:01 and HLA-E*01:03 alleles may differ in their capacity to interact with TCR receptors on T regulatory cells and the HLA-E*01:03 variant may be responsible for less effective TCR recognition [20].…”
Section: Discussionmentioning
confidence: 99%
“…27). Three other alleles ( HLA-DRB1*03 , HLA-DRB1*07 and HLA-DRB1*15 ) had a lower prevalence in patients with pemphigus vulgaris 26 , whereas HLA-E*0103 , a non-classical class IB allele, and a non-HLA marker encoding suppression of tumorigenicity 18 protein (ST18; a molecule that regulates apoptosis and inflammation) have both been associated with pemphigus vulgaris 28,29 . However, the association between ST18 and pemphigus vulgaris found in Jewish and Egyptian patients was not confirmed in German patients, suggesting that ST18-associated variants may predispose to pemphigus vulgaris in a population-specific manner 29 .…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…From several clinical studies, it has been found that there is also genetic susceptibility to PV, showing a significant correlation between several HLA class II alleles (such as DRB1*04, DRB1*08 and DRB1*14) and the disease . Numerous polymorphisms of HLA‐II have been identified throughout several populations of PV patients, as this susceptibility may be variable by ethnicity . Following binding to the self‐antigen, Dsg3 is subsequently internalized and processed in the T cells before being presented together with the related HLA molecules to activate B cells for secretion of pathogenic autoantibodies.…”
Section: Loss Of T‐cell Self‐tolerance In Pemphigusmentioning
confidence: 99%
“…23,[26][27][28] Numerous polymorphisms of HLA-II have been identified throughout several populations of PV patients, as this susceptibility may be variable by ethnicity. 26,[29][30][31] Following binding to the self-antigen, Dsg3 is subsequently internalized and processed in the T cells before being presented together with the related HLA molecules to activate B cells for secretion of pathogenic autoantibodies. Very recently, in the humanized HLA-DRB1*04:02-transgenic mouse model, the HLA-DRB1*04:02-restricted CD4 + T cells that are specifically reactive to human Dsg3 epitopes were shown to produce pathogenic pemphigus IgG antibodies.…”
Section: Loss Of T-cell Self-tolerance In Pemphigusmentioning
confidence: 99%